Frames of Reference and Kinship Terminology Systems - Bennardo, Giovanni (eScholarship, University of California, 2016)
The content of the spatial relationships module has been extensively studied and a fundamental part of such content is the concept of frame of reference; that is, a set of coordinates that generates an oriented space within which relationships between objects are established. There are three major types (and six subtypes) of frames of reference: the relative, the intrinsic, and the absolute. The content of the spatial relationships module has been proposed as being foundational to the development of both language and cognition. In this work I explore the possibility that the various types of frame of reference participate in the construction of the basic patterns of the kinship terminology systems: descriptive-Sudanese, bifurcate merging-Iroquois (also Crow and Omaha), classificatory and/or generational-Hawaiian (also classificatory-Dravidian), and lineal-Eskimo.